Pengaruh Harga, Lokasi, dan Fasilitas terhadap Keputusan Berkunjung Wisata Taman Sari di Yogyakarta - Meyta Salsa Hardina; Eka Sudarusman (Cakrawangsa Bisnis: Jurnal Ilmiah Mahasiswa, 2021)
Abstract The decision to visit attractions Taman Sari in Yogyakarta is influenced by several factors including price, location and tourist facilities. These three factors have an important role to improve the decision to visit. The problem of this research is the factors mentioned above partially. The purpose of this study was to determine and analyze the influence of price, location and facilities against the decision to visit attractions Taman Sari in Yogyakarta. This research population is all visitors who have visited at least 1 time or more to attractions Taman Sari Yogyakarta. The sample is determined with a model of Non-Probability Sampling with purposive sampling method. The sample size was determined according to hair et al to determine the number of samples by multiplying 5 times the number of question items, in this study there are 37 questions then obtained 185 respondents. Methods of data collection using questionnaires. The test used is test validity, reliability test, normality test, multicollinearity, heterokedastisitas, multiple linear regression test, t Test and test the coefficient of determination. The results of this study stated that the price effect is positive and not significant to the decision to visit attractions Taman Sari in Yogyakarta, while the variable location and facilities have a positive and significant impact on the decision to visit attractions Taman Sari Yogyakarta. The value of the coefficient of determination of this research at 57.2%.